Developing techno-economically sustainable methodologies for deep desulfurization using hydrodynamic cavitation - Suryawanshi, N.B. (Fuel, 2017)
The present work, for the first time, describes the efficacy of the cavitation process and compares the cavitation yield for two types of cavitation devices-one employing linear flow for the generation of cavities and other employing vortex flow. The process involves pre-programmed mixing of the organic and aqueous phases, and can be carried out using simple mechanical cavitating devices such as orifice or vortex diode. The process essentially exploits in situ generation of oxidising agents such as hydroxyl radicals for oxidative removal of sulfur. The efficiency of the process is strongly dependent on the nature of device apart from the nature of the organic phase. The effects of process parameters and engineering designs were established for three organic solvents (n-octane, toluene, n-octanol) for model sulfur compound-Thiophene. A very high removal to the extent of 95% was demonstrated. The results were also verified using commercial diesel. The cavitation yield is significantly higher for vortex diode compared to the orifice. The process has potential to provide a green approach for desulfurization of fuels or organics without the use of catalyst or external chemicals/reagents apart from newer engineering configurations for effective implementation of hydrodynamic cavitation in industrial practice and also appears to be economically sustainable.
Keywords: Fuel; Oxidation; Petroleum; Pollution Control; Sulphur Removal